Current Progress in the Endogenous Repair of Intervertebral Disk Degeneration Based on Progenitor Cells - Zhang, Yanbin; Hu, Yiqiang; Wang, Wentian; Guo, Zijun; Yang, Fan; Cai, Xianyi; Xiong, Liming (Frontiers in Bioengineering and Biotechnology, 2021)
Intervertebral disc (IVD) degeneration is one of the most common musculoskeletal disease. Current clinical treatment paradigms for IVD degeneration cannot completely restore the structural and biomechanical functions of the IVD. Bio-therapeutic techniques focused on progenitor/stem cells, especially IVD progenitor cells, provide promising options for the treatment of IVD degeneration. Endogenous repair is an important self-repair mechanism in IVD that can allow the IVD to maintain a long-term homeostasis. The progenitor cells within IVD play a significant role in IVD endogenous repair. Improving the adverse microenvironment in degenerative IVD and promoting progenitor cell migration might be important strategies for implementation of the modulation of endogenous repair of IVD. Here, we not only reviewed the research status of treatment of degenerative IVD based on IVD progenitor cells, but also emphasized the concept of endogenous repair of IVD and discussed the potential new research direction of IVD endogenous repair.